Glucose regulation by modified boronic acid-sulfobetaine zwitterionic nanogels – a non-hormonal strategy for the potential treatment of hyperglycemia. Issue 21 (21st May 2019) - GhavamiNejad, Amin; Lu, Brian; Giacca, Adria; Wu, Xiao Yu
Abstract : We synthesized a new glucose-responsive nanogel and demonstrated its potential as a non-hormonal treatment strategy for regulating blood glucose level. Abstract : We have introduced a non-hormonal hyperglycemia treatment strategy by using an injectable glucose-responsive boronic acid- zwitterionic nanogel. The synthesized system, similar to an artificial liver, is capable of storing/releasing glucose at high/low blood glucose concentrations. In vivo performance revealed that the injection of the nanogels can effectively regulate blood glucose in type 1 diabetic rats for at least 6 hours.